2022
DOI: 10.21203/rs.3.rs-2122822/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dominant changes in centre Fe atom of decamethyl-ferrocene from ferrocene in methylation

Abstract: Staggered decamethyl-ferrocence (*Fc) becomes the lower energy conformer at low temperature, whereas the eclipsed conformer of ferrocence (Fc) is more stable. The powerful infrared (IR) spectroscopy which has remarkably provided signatures of ferrocene (Fc) in eclipsed and staggered conformers recently is employed to investigate methylation of Fc. The most significant consequences of the full methylation of Fc in the IR spectra are the blue shift of the band at ~800 cm-1 in Fc to ~1500 cm-1 in *Fc, and the ban… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…10 Another CMS leading innovation case is the decade long theory guided (synchrotron sourced) spectroscopic study of ferrocene (Fc). [27][28][29][30][31][32][33][34][35][36][37] The theoretical IR spectral discovery of the more stable Fc eclipsed conformer (D 5h ) 27 shed a light on Fc studies, led and suggested several new measurements of Fc and its derivatives. 38 In the seminal theoretical IR study of Fc, it conclusively revealed that Fc eclipsed (D 5h ) and staggered (D 5d ) conformers exhibit their unique IR fingerprints in the region of 400-500 cm À1 .…”
Section: Microwave and Infrared Spectroscopymentioning
confidence: 99%
See 3 more Smart Citations
“…10 Another CMS leading innovation case is the decade long theory guided (synchrotron sourced) spectroscopic study of ferrocene (Fc). [27][28][29][30][31][32][33][34][35][36][37] The theoretical IR spectral discovery of the more stable Fc eclipsed conformer (D 5h ) 27 shed a light on Fc studies, led and suggested several new measurements of Fc and its derivatives. 38 In the seminal theoretical IR study of Fc, it conclusively revealed that Fc eclipsed (D 5h ) and staggered (D 5d ) conformers exhibit their unique IR fingerprints in the region of 400-500 cm À1 .…”
Section: Microwave and Infrared Spectroscopymentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34][35][36][37] The theoretical IR spectral discovery of the more stable Fc eclipsed conformer (D 5h ) 27 shed a light on Fc studies, led and suggested several new measurements of Fc and its derivatives. 38 In the seminal theoretical IR study of Fc, it conclusively revealed that Fc eclipsed (D 5h ) and staggered (D 5d ) conformers exhibit their unique IR fingerprints in the region of 400-500 cm À1 . 27 That is, the IR band of Fc staggered (D 5d ) conformer does not split (the splitting of d = 2 cm À1 is sufficiently small not to be measured), whereas the band splits (d = 17 cm À1 ) in the same region for Fc eclipsed (D 5h ) conformer is measurable in almost all IR spectral measurements available.…”
Section: Microwave and Infrared Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations